The Proto-Indo-European Vowel System from the Typological Point of View - Matasović, Ranko (Array, 2003)
In this paper the proposed reconstructions of the PIE vowel system are examined from t typological point of view. It is argued that the monovocalic system is improable, while the maximalistic view of the PIE vowel system is unacceptable, ince all the alleged instances of PIE *a can be explained as containing *H2. The PIE long vowels *e and *o are best treated as short *e and *o with the additional suprasegmental feature of length. It is argued that it would be possible to reinterpret PIE *e as /a/, and PIE *o as "schwa" to achieve a typologically plausible reconstruction of the PIE vowel system.